Phytocoenology and habitat preference of Paeonia tenuifolia, a vulnerable species in Romania - Chirilă, Simona Dumitrița; Vassilev, Kiril (Biológia, 2024)
Paeonia tenuifolia is a rare steppe species that is protected in Romania. Anthropogenic influences have led to a decline in the size and number of P. tenuifolia populations. There is currently insufficient data on this species' phytocoenology and habitat preferences. Therefore, this study aimed to identify the habitat preferences of P . tenuifolia in Romania. 65 relevés from the Banat, Transylvania, and Dobrogea regions were analyzed to achieve this. The size of the plots varied from 25 m 2 to 200 m 2 . Agglomerative Hierarchical Clustering (AHC) was used to classify the vegetation, in the GINKGO program. The relationship between floristic composition and environmental variables was assessed using Detrended Correspondence Analysis (DCA) and Canonical Correspondence Analysis (CCA), in CANOCO. The environmental variables were represented by climatic variables (mean annual temperature, annual precipitation), topographic variables (elevation) and edaphic variables (pH, P, and K). The study results showed that AHC allowed the identification of 11 clusters. P . tenuifolia occurs most frequently in the associations Agropyro pontici - Thymetum zygioidis and Festuco rupicolae - Brachypodietum pinnati . CCA results imply strong relationships between floristic composition and annual precipitation (BIO12). Among the three analyzed regions, P. tenuifolia was confirmed only in the Dobrogea and Transylvania regions. Knowledge of the floristic composition and its correlation with environmental variables in the analyzed areas should guide future conservation strategies and management efforts.